2016
DOI: 10.1007/s11340-016-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of an Adaptively Tuned Dynamic Absorber Incorporating Magnetorheological Elastomer with Self-Sensing Property

Abstract: The magnetorheological elastomer (MRE) is known to belong to a class of smart materials whose elastic properties can be varied by an externally applied magnetic field. In addition to the property of the field-dependent stiffness change of the MRE, the electrical resistance of the composite is also changed by the induced strain, thereby providing a new selfsensing feature. In the present study, a novel, dynamic vibration absorber is developed using an MRE with a self-sensing function and adaptability. The natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The natural frequency of all three MRE devices increased by 183 percent for the shear device, 473 percent for the longitudinal device, and 507 percent for the squeeze mode device when the field strength was between 0 and 183 kA/m. Recently, Komatsuzaki et al [87] created a self-sensing MRE-based dynamic vibration absorber. The external magnetic field can influence the elastomer's natural frequency and electrical resistance.…”
Section: Itymentioning
confidence: 99%
“…The natural frequency of all three MRE devices increased by 183 percent for the shear device, 473 percent for the longitudinal device, and 507 percent for the squeeze mode device when the field strength was between 0 and 183 kA/m. Recently, Komatsuzaki et al [87] created a self-sensing MRE-based dynamic vibration absorber. The external magnetic field can influence the elastomer's natural frequency and electrical resistance.…”
Section: Itymentioning
confidence: 99%
“…Then, these chain-like structures become resistant to external forces (Carlson and Jolly, 2000 ). This unique feature makes MRCs useful in some applications such as brakes (Yu et al, 2016 ), dynamic vibration absorbers (Komatsuzaki et al, 2016 ), and even industrial robot grippers (Pettrtsson et al, 2010 ; Nishida et al, 2016 ). Current studies have mainly focused on dynamic properties of the material (Xu et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al [9] developed a tunable vibration absorber (TVA) made of MREs that increases in stiffness by 118% when a current of 1.5 A is applied to the electromagnet. Komatsuzaki et al [10] proposed a TVA with a tuning range of 25.8–37.4 Hz under a magnetic field of 316 mT and a current of 6 A. Kim et al [7] designed an MRE TVA for a linear compressor. The system frequency response varies from 32 to 60 Hz as the stiffness of the MRE changes by 252%, which is achieved under a magnetic field of 240 mT.…”
Section: Introductionmentioning
confidence: 99%
“…Using the properties of the impedance change of the MRE by an external magnetic field, MREs have been studied as sensors for a vibration absorber system. Komatsuzaki et al [10,16] developed a dynamic TVA based on MREs. They observed that change in the MRE resistance is dependent on the frequency of the strain resulting from vibration.…”
Section: Introductionmentioning
confidence: 99%